2012
DOI: 10.1074/jbc.m111.312330
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-induced Enhancement of Factor VIIa Activity through Distinct Allosteric Pathways

Abstract: Background:The enzymatic activity of coagulation factor VIIa (FVIIa) is allosterically controlled by tissue factor (TF). Results: Monoclonal antibodies (mAbs) can allosterically augment the intrinsic activity of FVIIa through mechanisms distinct from that of TF. Conclusion: Different modes of allosteric activation of FVIIa appear to exist. Significance: Artificial activators of FVIIa can be tools to study the zymogen-to-protease transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…[11][12][13] Soon after the development of monoclonal antibody technology, antibodies against FVII and FVIIa were generated. [14][15][16][17][18] Of note, many of them recognize both the active and zymogen forms of FVII.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Soon after the development of monoclonal antibody technology, antibodies against FVII and FVIIa were generated. [14][15][16][17][18] Of note, many of them recognize both the active and zymogen forms of FVII.…”
Section: Introductionmentioning
confidence: 99%
“…Philippou et al generated a polyclonal antibody directed against the C-terminal part of the FVIIa light chain, which displayed >3000-fold greater reactivity to FVIIa than FVII. 19 Andersen et al 18 reported on antibodies that show preferential binding to FVIIa and stimulated FVIIa activity. Most recently, a llama-derived single-domain antibody (sdAb) that binds to FVIIa but not to FVII has been described.…”
Section: Introductionmentioning
confidence: 99%
“…On TF, a membrane proximal patch has been defined and distinct recognition sites have been localized on FVIIa ( 17 – 19 ). Since the enhancement of proteolytic activity by sTF in solution is only a few hundred-fold, of which allosteric activation accounts for the major part ( 15 , 20 ), exosite-mediated FX recognition appears to be realized primarily on the membrane surface.…”
mentioning
confidence: 99%
“…The amidolytic activity of FVIIa was measured using the chromogenic substrates Chromozym t-PA or Spectrozyme FXa, as previously described (Andersen et al, 2012). In brief, a 96-well plate was blocked overnight in 200 µL Assay Buffer (AB) containing; 20 mM HEPES (pH 7.8), 150 mM NaCl, 5 mM CaCl 2 , 0.1 % PEG 8000, 0.5 % BSA, at 4 °C.…”
Section: Fvii and Fx Enzyme Activity Assaysmentioning
confidence: 99%
“…FX activation by TF-FVIIa complex was also measured using chromogenic assay as described (Andersen et al, 2012). The activity of FX was determined by incubating 100 µL AB containing 200 nM FX with 100 nM rFVIIa, or with 10 nM rFVIIa and 200 nM TF (Thromborel ® S), incorporated into phospholipid as recommended (Kelley et al, 1997) of 6 µL TriniCLOT ™ aPTT HS, for 1 hr at 37 °C.…”
Section: Fvii and Fx Enzyme Activity Assaysmentioning
confidence: 99%